Model-based concerns mashups for mobile hypermedia - Challiol, Cecilia; Rossi, Gustavo Héctor; Gordillo, Silvia Ethel; Fortier, Andrés (2008)
Mobile (or Physical) Hypermedia combines the navigational style typical of Web applications with the functionality of location and context-aware software. Users explore digital and physical relationships while accessing to information about their actual location, e.g. the object in front of them. Similar to conventional Web applications one might suffer usability problems when dealing with multiple informational concerns, but the situation gets worse because of screen size issues, the need to avoid user distraction, etc. In this paper we outline our modelbased approach for building mobile hypermedia applications by combining (mashing up) information corresponding to multiple concerns in a modular, usable way. Architectural issues are discussed and a simple example is presented together with its implementation.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 20/03/2009)
Proceedings of 6th International Conferences on the Advances of Mobile Computing and Multimedia - MoMM 2008, ACM Press 2008.
Keywords: ARQUITECTURAS DE DOMINIO ESPECÍFICO; COMPUTACIÓN MÓVIL; APLICACIONES SENSIBLES AL CONTEXTO; APLICACIONES HIPERMEDIA